Implementing a Mineral Water Gallon Counter Device Based on a Website Using Infrared Sensors - Dhafa Kamil; Ester Angeline; Ivan De Nerol; Rafi Rasyid Parmana (Batrisya Education, 2024)
This research discusses the development of a mineral water gallon counter system using infrared sensors integrated into a website interface to increase the efficiency of distribution management in the company. This system uses infrared sensor technology to automatically detect the movement of gallons of mineral water at entry and exit points. The detection data is processed and presented via a web interface that can be accessed in real time, providing accurate information on the number of gallons entering and leaving. The research methodology involves the development of hardware and software and the results show that this system can increase the company's operational efficiency and provide easy online monitoring of mineral water distribution. The implications of this research are expected to make a positive contribution to the optimisation of the distribution process and the management of mineral water stocks in companies.